Theory of Wealth Accumulation Differences Considering Modern Net Savings Gradualism: Impact of Unresolved Long Run Differences in Wealth Accumulation on the Annualized Net Savings in USA - Curtis, Jr., Dr. James E. (Modern Perspectives in Economics, Business and Management Vol. 9, 2021)
In Wealth and Faith, James Curtis Jr (2010)[1] wrote…unexplained differences (in white-black wealth) in states that abolished slavery (as a result of) the Civil War were 10 percent higher than unexplained effects in states that abolished slavery well before the Civil War….(Combining this 10 percent gap with persistent) magnitudes of the unexplained effects (in white-black wealth differences) … we cannot reject the existence of a negatively bounded correlation between the duration of time from enslavement and the magnitude of unexplained differences in (white-black) wealth.